The Effect of Training on Quality Server Service and Guest Satisfaction in F&B Outlet The Melio Enim Hotel - Noholo, Gilang Ramadhan; Sinuraya, Enos Julvirta; Rahmania Ananda Puteri; Wientor Rah Mada; Muhammad Algi Fachri Akbar (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2025)
This study aims to determine: (1) waitress training; (2) the quality of the service of waiters; (3) customer satisfaction; (4) the effect of training on customer satisfaction; (5) the effect of training on service quality; (6) the effect of service quality on customer satisfaction; (7) the effect of training on customer satisfaction through service quality. This type of research is a descriptive study with a quantitative approach. A sample of 120 respondents who stayed or visited Woza Restaurant D 'Riam Riverside Ressort Ciwidey and used the population were a number of restaurant employees so there was a need to equalize the number of respondents in data processing. The sampling technique used was accidental sampling and data collection methods using a questionnaire. Analysis of the data used is path analysis (path analysis), MSI (Method of Successive Intervals), and regression tests and are inferential. The results of data analysis revealed that: (1) the training variables were declared good; (2) the variable quality of service is stated sufficient; (3) the customer satisfaction variable is stated sufficient; (4) the training variable does not have a significant direct effect on the customer satisfaction variable; (5) training variables have a significant influence on service quality variables; (6) service quality variables have a significant influence on customer satisfaction variables; (7) the service quality variable successfully mediated the training variable on customer satisfaction.